2015
DOI: 10.1177/0003489415589364
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Flora and Antibiotic Resistance in Peritonsillar Abscesses in Upstate New York

Abstract: β- and α-hemolytic Streptococci, Neisseria, and Streptococcus milleri are the most common pathogens. Streptococcus milleri is more common in adults, and β-hemolytic streptococcus is more common in children. Resistance to clindamycin and erythromycin is common in Streptococci and Staphylococci, and penicillin resistance is common in Staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“… Streptococcus pyogenes Prevotella sp. Plum et al (2015) 44 USA 2002–2012 69 Streptococcus milleri in adults β-hemolytic streptococcus in children Lepelletier et al (2016) 36 French 2009–2012 412 Group A streptococci Fusobacterium spp. Tachibana et al (2016) 45 Japan 2008–213 100 Streptococcus viridans Fusobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“… Streptococcus pyogenes Prevotella sp. Plum et al (2015) 44 USA 2002–2012 69 Streptococcus milleri in adults β-hemolytic streptococcus in children Lepelletier et al (2016) 36 French 2009–2012 412 Group A streptococci Fusobacterium spp. Tachibana et al (2016) 45 Japan 2008–213 100 Streptococcus viridans Fusobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…A rapid antigen test was positive for Group A Streptococcus , H. cinaedi was detected on blood culture, and Group C Streptococcus was detected in the drainage fluid from peritonsillar abscess after antibiotic administration. Peritonsillar abscesses are often polymicrobial, and it has been reported that 62% of cases are mixed infections [7] . Some individuals are carriers of Group A Streptococcus , and positive antigen results for Group A Streptococcus may indicate either a carrier state or active infection [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…This resistance pattern is in keeping with recent reports of rising antibiotic resistance to Clindamycin and suggests we should consider a shift in our prescribing practice. 2,27,28 Most of our patients were also given dexamethasone in the ED. Literature has shown that corticosteroids in PTA treatment reduce pain and improve clinical course.…”
Section: Discussionmentioning
confidence: 99%